**Answer:**

^F^ is the answer

**Step-by-step explanation:**

The first step to solve this equation is to move the variable to the left side of the equation and change its sign

4z + 3z + 5 = -8

Move the constant to the right side of the equation and change its sign

4z + 3z = -8 - 5

Collect the like terms on the left side of the equation

7z = -8 - 5

Calculate the difference

7z = -13

Lastly,, divide both sides of the equation by 7 to find out what z is

z = -

This means that z in your equation is -

,, or 1

when simplified.

Let me know if you have any further questions

:)

**Answer:**

the answer to your question is 24 units,

**Step-by-step explanation:**

**it's right on edge 2021**

F^-1(x)=x is the inverse function

**Answer:**

3,10

**Step-by-step explanation:**

X is first so subtract it by 2 and you get 3. then your going up with Y so 3+7=10. so pretty much get a graph